Bilirubin toxicity to human erythrocytes: a review - Brito, Maria Alexandra (2015)
Neonatal jaundice, a physiologic condition reflecting the interplay between developmentally modulated changes in bilirubin production and metabolism, affects virtually all newborn infants. Usually, it is an entirely benign process that is resolved at the